2021
DOI: 10.1109/access.2021.3134207
|View full text |Cite
|
Sign up to set email alerts
|

Rate-Splitting Multiple Access for URLLC Uplink in Physical Layer Network Slicing With eMBB

Abstract: In this paper, we investigate the problem of heterogeneous service coexistence in the scope of 5G and beyond (B5G) networks, where multiple ultra-reliable low-latency communication (URLLC) and enhanced mobile broadband (eMBB) users are connected to a common base station (BS), sharing physical network resources. In contrast to the orthogonal multiple access (OMA) and non-orthogonal multiple access (NOMA) usually adopted in literature, in this work we employ rate splitting multiple access (RSMA) for URLLC transm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 41 publications
(47 reference statements)
0
12
0
Order By: Relevance
“…Nonetheless, because of its powerful interference management capabilities, RSMA significantly benefits uplink transmission and can enable core services where users have intermittent access behaviour such as URLLC and mMTC. Moreover, RSMA is capable of enabling different combinations of core services to serve users with heterogeneous profiles [12].…”
Section: B Rsma In the Uplinkmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonetheless, because of its powerful interference management capabilities, RSMA significantly benefits uplink transmission and can enable core services where users have intermittent access behaviour such as URLLC and mMTC. Moreover, RSMA is capable of enabling different combinations of core services to serve users with heterogeneous profiles [12].…”
Section: B Rsma In the Uplinkmentioning
confidence: 99%
“…6) Network slicing: In 6G, a combination of services such as eMBB and URLLC will require the network to serve heterogeneous user profiles with diverse QoS requirements. [12] utilizes network slicing to share the resources among users with different profiles and shows that RSMA outperforms OMA and NOMA schemes for URLLC service even in the presence of interference from eMBB users. In the future, the role of RSMA to mitigate impact of imperfect CSIT and ensure security in allocation of slice resources to users of different profiles are worth investigating.…”
Section: Applications and Future Workmentioning
confidence: 99%
“…Recently, uplink RSMA has been applied to realize physical layer network slicing for ultrareliable and low-latency (URLLC) and enhanced mobile broadband communications (eMMB) [27]. Also, RSMA has been used to support URLLC and eMMB in 6G NR downlink transmissions [28].…”
Section: A Related Workmentioning
confidence: 99%
“…τ is the tolerance of convergence. Since the solution of Problem (17) at iteration n − 1 is a feasible point of Problem (17) at iteration n and the transmit power constraints (11g) and (11h), the objective function t is monotonically increasing which implies that the convergence of this proposed SCAbased algorithm is guaranteed. −1] and denote the optimal objective as t * and the optimal variables as P * , θ * , ρ * ;…”
Section: Problem Formulation and Algorithmmentioning
confidence: 99%
“…Motivated by the trade-off between achievable rate and error probability, the error probabilities have been derived for NOMA in Additive White Gaussian Noise (AWGN) channel and Rayleigh fading channel with FBL in [13]- [16], and NOMA was shown to achieve higher effective throughput and reduced latency compared to OMA. The authors in [17] have shown RSMA can outperform OMA and NOMA in a network slicing scenario.…”
Section: Introductionmentioning
confidence: 99%